Through Silicon Via stress characterization - Thuy Dao; Triyoso, D.H.; Petras, M.; Canonico, M. (2009 IEEE International Conference on IC Design and Technology, 2009)
In this paper, we will present Micro Raman stress data of Through Silicon Vias (TSV) with different shapes and sizes & spacing, and discuss design considerations.